2016
DOI: 10.4209/aaqr.2015.05.0372
|View full text |Cite
|
Sign up to set email alerts
|

Excess Lifetime Cancer Risk Assessment of Volatile Organic Compounds Emitted from a Petrochemical Industrial Complex

Abstract: A health risk assessment for the Lin-Yuan Petrochemical Industrial Complex (LYPIC) in southern Taiwan was conducted in this study. The main aims of the study were to develop an emission inventory for the 21 processing plants in the LYPIC, conduct hazard identification based on the emission inventory, perform an exposure assessment by applying air dispersion modeling to obtain the annual average concentration of hazardous air pollutants near the LYPIC, and estimate the lifetime risk of cancer associated with vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Also, the LCR for acrylonitrile was calculated between 2.8 ×10 -5 to 4.3 ×10 -5 , which is in the range of potential risk. 38 A study conducted by Bricarello in collaboration with the California State Resource Organization (ARB) on the measurement of acrylonitrile in ambient air using solid absorber tubes and heat recovery method in 2010 showed that in the presence of inhalation at a concentration of 0.65 μg/m 3 , the possible carcinogenic rate of 65 cancers per million was reported, or in other words, the carcinogenicity index was estimated to be 6.5 × 10 -5 and stated that the difference in the results showed that the final concentration of the samples depended on the condition of the sample. Further studies showed that the time between measurement and analysis of samples and possibly the room temperature at the sampling time play a significant role in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the LCR for acrylonitrile was calculated between 2.8 ×10 -5 to 4.3 ×10 -5 , which is in the range of potential risk. 38 A study conducted by Bricarello in collaboration with the California State Resource Organization (ARB) on the measurement of acrylonitrile in ambient air using solid absorber tubes and heat recovery method in 2010 showed that in the presence of inhalation at a concentration of 0.65 μg/m 3 , the possible carcinogenic rate of 65 cancers per million was reported, or in other words, the carcinogenicity index was estimated to be 6.5 × 10 -5 and stated that the difference in the results showed that the final concentration of the samples depended on the condition of the sample. Further studies showed that the time between measurement and analysis of samples and possibly the room temperature at the sampling time play a significant role in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Because formaldehyde is classified as a Group 1 carcinogen by the International Agency for Research on Cancer, there is popular worry about using woody formaldehyde bio-based products. Formaldehyde is listed as a major indoor pollutant by many countries (Chen et al 2016). Many laws and regulations prohibit the addition of formaldehyde in food, cosmetics, and other products that are directly consumed and come into contact with the skin.…”
Section: Controversies Of Formaldehyde Health Hazardsmentioning
confidence: 99%
“…Despite general agreement on observations, such as light alkanes being the most abundant VOC species in refinery perimeter areas [2,27], studies have reached different conclusions regarding the impacts of refinery emissions on nearby ambient VOC enhancement. While some works have found elevated VOC concentrations when compared to background sites and urban locations [8][9][10]14,28,29], other studies conducted at different sites worldwide have reported no major impact from petroleum refineries emissions on neighboring VOC and PAH atmospheric levels [3][4][5][6][7]. While Na et al [14] reported higher concentrations of PM and VOCs nearby petroleum refineries in South Korea when compared to a downtown location, Baltrenas et al [4] and Kalabokas et al [5] found similar or lower VOC levels in Lithuania and Greece refinery neighboring areas when compared to urban centers in those countries.…”
Section: Introductionmentioning
confidence: 99%